A 3D parallel shrinking algorithm - Palágyi, Kálmán (Acta Cybernetica, 2001)
Shrinking is a frequently used preprocessing step in image processing. This paper presents an efficient 3D parallel shrinking algorithm for transforming a binary object into its topological kernel. The applied strategy is called directional: each iteration step is composed of six subiterations each of which can be executed in parallel. The algorithm makes easy implementation possible, since deletable points are given by 3 x 3 x 3 matching templates. The topological correctness of the algorithm is proved for (26,6) binary pictures.